Financial instability and economic activity - Ines Fortin; Jaroslava Hlouskova; Leopold Sögner (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2021)
We estimate new indices measuring financial and economic (in)stability in Austria and in the euro area. Instead of estimating the level of (in)stability in a financial or economic system we measure the degree of predictability of (in)stability, where our methodological approach is based on the uncertainty index of Jurado, Ludvigson and Ng (2015). We perform an impulse response analysis in a vector error correction framework, where we focus on the impact of uncertainty shocks on industrial production, employment and the stock market. We find that financial uncertainty shows a strong significantly negative impact on the stock market, for both Austria and the euro area, while economic uncertainty shows a strong significantly negative impact on the economic variables for the euro area. We also perform a forecasting analysis, where we assess the merits of uncertainty indicators for forecasting industrial production, employment and the stock market, using different forecast performance measures. The results suggest that financial uncertainty improves the forecasts of the stock market while economic uncertainty improves the forecasts of macroeconomic variables. We also use aggregate banking data to construct an augmented financial uncertainty index and examine whether models including this augmented financial uncertainty index outperform models including the original financial uncertainty index in terms of forecasting.
Keywords: C53; G01; G20; E44; 330; financial (in)stability; uncertainty; financial crisis; forecasting; stochastic volatility; factor models